Do EU fiscal rules support or hinder counter-cyclical fiscal policy? - Martin Larch; Eloïse Orseau; Wouter van der Wielen (European Commission, Joint Research Centre (JRC), 2020)
Rather than stabilising aggregate demand, discretionary fiscal policy tends to amplify cyclical fluctuations of output. The commonly accepted reasons are political economy and uncertainty. In the EU, the pro-cyclical nature of discretionary fiscal policy has also been associated with the commonly agreed fiscal rules, which, for some observers, unduly limit the scope for stabilising output. Using panel data covering close to 50 EU and non-EU countries, we provide evidence that the uncertainty around output gap estimates is not a convincing explanation for pro-cyclical policies. Discretionary measures remain ill-timed from a stabilisation perspective even when observable and politically more meaningful indicators of the cycle are used. We also show that deviations from fiscal rules and the accumulation of government debt foster pro-cyclical fiscal policy. Lawmakers can run discretionary fiscal policy measures based on political economy considerations up to a point. Once debt grows too high, they are forced to implement fiscal consolidation measures regardless of the cycle. More generally, there is no fiscal rule, which, if consistently ignored, safeguards the opportunity to stabilise output with discretionary fiscal policy measures. Complying with fiscal rules that are designed to keep a steady course in the face of cyclical fluctuation is conducive to counter-cyclical fiscal policy making.
Keywords: C23; E61; E62; H30; H60; 330; fiscal policy; fiscal rules; fiscal stabilisation; counter-cyclical policy; dynamic panel models